Influence of Single Parenting and Family Size on Learning Outcome Among Primary School Pupils in Gwale, Kano State - Musa , Ibrahim; Abdullahi, Rukayya; Otaru, Bernard Meshach; Sani Mainagge, Ibrahim Muhammad (International Journal of Educational Management, 2021)
The study examined the influence of single parenting and family size on learning outcome among primary school pupils in Gwale, Kano State. The expo facto research design was adopted for the study. Three hundred pupils were randomly selected and were used as participants. The instrument for data collection was researcher’s made questionnaire tagged “Learning Outcome Questionnaire” (LOQ). Three hypotheses were formulated and tested at 0.05 level of significance. The data were analyzed using t-test statistical tool. The findings indicated that there was significant difference in the learning outcome between pupils from single parents and those from small family size in favour of pupils from small family size. The study further found that there was significant difference in learning outcome between pupils from single parents and those from large family size in favour of pupils from large family size. The study also revealed that there was significant difference in learning outcome between pupils from small family size and those from large family size in favour of pupils from small family size. It was recommended that school management should encourage the single parents to be involved in their children’s academic work. Finally, parents should be sensitized on the need to raise small families in order to provide them with educational needs that will motivate the children to learn effectively and perform satisfactorily in their academic achievement